Mediasi Job Satisfaction pada Pengaruh Person-Job Fit, Person-Organization Fit, terhadap Organizational Citizenship Behavior di PDAM Kulon Progo - Mubarkah, Ahmad Hanif; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (Universitas Proklamasi 45, 2024)
This study aims to analyze the mediating role of job satisfaction on the effect of person-job fit and person-organization fit on the organizational citizenship behavior of PDAM Tirta Binangun Kulon Progo employees. This research is a quantitative study that uses primary data collection with questionnaire instruments. The study involved 131 employees whose data were taken by census. The data were processed using multiple linear regression analysis. The results stated that person-job fit and person-organizational fit had a positive and significant impact on organizational citizenship behavior partially. Person-organizational, person-job fit, and job satisfaction have a positive and significant effect partially on organizational citizenship behavior. Job satisfaction is proven to mediate the effect of person-job fit and person-organizational fit on organizational citizenship behavior. Strengthening antecedents is an important aspect for organizations when organizations make policies to improve employee organizational citizenship behavior.